The Role of Demoralization and Meaning in Life (DEMIL) in Influencing Suicidal Ideation Among Patients Affected by Chronic Pain: Protocol of a Single-Center, Observational, Case-Control Study - Costanza, Alessandra; Chytas, Vasileios; Mazzola, Viridiana; Piguet, Valérie; Desmeules, Jules; Bondolfi, Guido; Cedraschi, Christine (JMIR Research Protocols, 2020)
BackgroundChronic pain is a significant risk factor for suicidal ideation (SI) and suicidal behavior (SB), including a 20%-40% prevalence rate of SI, a prevalence between 5% and 14% of suicide attempts, and a doubled risk of death by suicide in patients with chronic pain compared to controls. In most studies, associations between chronic pain and suicidality are robust, even after adjusting for the effect of sociodemographics and psychiatric comorbidity, and particularly for depressive conditions. A number of specific conditions that can modulate suicidality risk in patients with chronic pain have been investigated, but there is a need for their more specific characterization. Numerous recent studies have shown that demoralization and meaning in life (MiL) constructs affect suicidality as risk and protective factors, respectively. These constructs have been mainly investigated in patients with somatic illness and in community-dwelling individuals who may present with SI or SB independently of a psychiatric diagnosis of depression. However, a paucity of studies investigated them in suicidal patients affected by chronic pain. ObjectiveThe primary objective of this project is to investigate the relationship between demoralization and MiL on SI risk in patients with chronic pain. The secondary objectives are (1) to test whether demoralization can occur independently of depression in patients with chronic pain and SI, (2) to examine whether the expected association between demoralization and SI may be explained by a sole dimension of demoralization: hopelessness, (3) to examine whether the presence of MiL, but not the search for MiL, is associated with less SI, and (4) to explore whether previously described MiL profiles (ie, high presence-high search, high presence-low search, moderate presence-moderate search, low presence-low search, and low presence-high search) emerge in our cohort. MethodsThis project is a single-center, observational, case-control study—the Demoralization and Meaning in Life (DEMiL) study—conducted by the Division of Clinical Pharmacology and Toxicology, the Multidisciplinary Pain Centre, and the Service of Liaison Psychiatry and Crisis Intervention at the Geneva University Hospitals. Self- and hetero-administered questionnaires were conducted among patients and controls, matched by age and gender. The Ethics Committee of the Canton of Geneva approved the scientific utilization of collected data (project No. 2017-02138; decision dated January 25, 2018). Data have been analyzed with SPSS, version 23.0, software (IBM Corp). ResultsFrom March 1, 2018, to November 30, 2019, 70 patients and 70 controls were enrolled. Statistical analyses are still in progress and are expected to be finalized in November 2020. To date, we did not observe any unfavorable event for which a causal relationship with the collection of health-related personal data could be ruled out. Results of this study are expected to form the basis for possible prevention and psychotherapeutic interventions oriented toward demoralization and MiL constructs for suicidal patients with chronic pain. ConclusionsThe interest in exploring demoralization and MiL in chronic pain patients with SI arises from the common clinical observation that experiencing chronic pain often requires a revision of one’s life goals and expectations. Hence, the impact of chronic pain is not limited to patients’ biopsychosocial functioning, but it affects the existential domain as well. The major clinical implications in suicidal patients with chronic pain consist in trying to (1) delineate a more precise and individualized suicide risk profile, (2) improve detection and prevention strategies by investigating SI also in individuals who do not present with a clinically diagnosed depression, and (3) enhance the panel of interventions by broadening supportive or psychotherapeutic actions, taking into consideration the existential condition of a person who suffers and strives to deal with his or her suffering. International Registered Report Identifier (IRRID)DERR1-10.2196/24882